Experimental and numerical analysis of mechanical characteristics of fused deposition processed sandwich thin-walled structures - Avramov K.; Derevianko І.; Uspensky B.; Salenko A.; Maksymenko-Sheiko K.; Chernobryvko M. (НТУ "ДП", 2025)
Approach for mechanical characteristic experimental analysis of honeycomb manufactured by fused deposition modeling is uggested. Experimental analyses of shear and tension of the honeycombs specimens fabricated from PLA and ULTEM 9085 materials are performed. The experimental studies are accompanied by the finite element simulations of the shear and the tension experiments. It is shown experimentally, that the geometrical nonlinearity must be accounted for the honeycomb tension analysis. The force-displacement response of honeycomb tension is nonlinear due to accounting of the geometrical nonlinearity behavior of the structure.
Keywords: honeycomb core; fused deposition modeling; shear; force-displacement response.